Real-world retrospective cohort study evaluating the tolerability of immune globulin intravenous 10% (BIVIGAM®) - Van Anglen, Lucinda J.; Luu, Quyen; Rosenbach, Kevin P.; Herrscher, Richard F. (Frontiers in Immunology, 2025)
IntroductionIntravenous immune globulin 10% liquid (IVIG 10%) is used in the treatment of primary immunodeficiency (PID). Originally approved in 2012 and then voluntarily withdrawn in 2016, IVIG 10% (BIVIGAM®) underwent manufacturing process improvements by a new manufacturer and was reintroduced to the US market in 2019. The purpose of this real-world study is to assess the tolerability of BIVIGAM in an outpatient setting.MethodsAn observational, retrospective analysis was performed using a random sample of patients who initiated BIVIGAM from 8/2021-5/2022 in 15 US outpatient physician office infusion centers. Patient data collected from electronic medical records included baseline characteristics, BIVIGAM treatment details, adverse events (AEs) and clinical laboratory data for 6 months following initiation.ResultsA total of 60 patients treated with BIVIGAM were included. The mean age was 74 ± 8.2 years, 82% were female, and 90% had prior experience with immune globulin therapy. Treatment diagnoses were PID-related in the majority of patients (58,97%).There were 346 BIVIGAM infusions (mean of 5.8 ± 2.6 infusions per patient, mean dose of 492 ± 200.8 mg/kg),titrated upward over a mean of 80 ± 27.9 minutes to a final maximum mean infusion rate of 158 ± 28.8 mL/hr. Pre-medications were used in 83% of patients during 266 infusions. Forty-six AEs were patients (38.3%), resulting in an overall AE rate per infusion of 0.13 per patient year.DiscussionBIVIGAM was well-tolerated within this real-world outpatient setting. Infusion-related adverse reactions were low. This study provides the largest real-world evaluation of reformulated BIVIGAM in outpatient practice.